A first principle study on sensing properties of quasi-planer born (B36 borophene) towards COS, SO2, H2S and CS2 gases - Kadhim M.M.; Taban T.Z.; Shadhar M.H.; Jasem H.; Hachim S.K.; Rheima A.M.; Masileno A. (Elsevier B.V., 2023)
Density functional theory; Density of gases; Dipole moment; Electric dipole moments; Conductivity; CS2 gas; Density-functional-theory; Electric-dipole moment; Electronic conductivity; Electronic sensors; First-principle study; Interaction; Sensing property; Short recovery time; Desorption